2013
DOI: 10.1007/s12013-013-9601-0
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Expression of M2-PK and VEGF in Patients with Advanced Gastric Cancer

Abstract: Glycolytic pyruvate kinase isoenzyme type M2 (M2-PK) plays a key role in tumor metabolism and energy production. Vascular endothelial growth factor (VEGF) is critical in regulating angiogenesis which is an essential process required for tumor growth and metastasis. These two genes may function in accordance with tumor development. The purpose of this study was to investigate the relationship between the expression of M2-PK and VEGF, and their association with clinicopathological features in patients with advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Previous findings have indicated that PKM2 and LDH5 are commonly overexpressed in a broad spectrum of cancers and are required for tumour metabolism and growth. Overexpression of PKM2 or LDH5 was associated significantly with adverse clinicopathological features, including advanced tumour stage, lymph node metastasis and unfavourable prognosis in diverse cancers including head and neck squamous cell carcinoma . Consistent with these previous findings, our data from tongue cancerous cell lines indicated that PKM2 and LDH5 protein were both up‐regulated significantly compared with non‐tumorigenic oral epithelial cells.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Previous findings have indicated that PKM2 and LDH5 are commonly overexpressed in a broad spectrum of cancers and are required for tumour metabolism and growth. Overexpression of PKM2 or LDH5 was associated significantly with adverse clinicopathological features, including advanced tumour stage, lymph node metastasis and unfavourable prognosis in diverse cancers including head and neck squamous cell carcinoma . Consistent with these previous findings, our data from tongue cancerous cell lines indicated that PKM2 and LDH5 protein were both up‐regulated significantly compared with non‐tumorigenic oral epithelial cells.…”
Section: Discussionsupporting
confidence: 89%
“…Until now, several clinicopathological prognostic indicators have been proposed, including clinical stage, histological grade and cervical node metastasis . Previous findings have suggested that PKM2 and LDH5 expression are of prognostic significance in a variety of malignancies . Our results indicate clearly that high PKM2 or LDH5 expression associates significantly with decreased overall patient survival.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…6,7 This findings have been supported by the facts that abnormal overexpression of PKM2 has been frequently observed in multiple human cancers and its upregulation correlates with cancer aggressive behaviors and clinicopathological features, therapeutic resistance and unfavorable treatment outcomes. [8][9][10] Further evidence linking PKM2 to tumorigenesis also comes from previous findings that PKM2 depletion via either RNA interference or pharmacologic agents impaired cancer cell proliferation, induced cell apoptosis, enhanced therapeutic sensitivity and decreased tumorigenicity both in vitro and in vivo. [11][12][13] Collectively, these findings have provided proof-of-principle that PKM2 is the bona fide oncogene mediating cancer metabolic reprogramming as well as an attractive therapeutic target.…”
Section: Introductionmentioning
confidence: 94%